A new species of the genus Eudorylaimus Andrássy, 1959 (Nematoda: (Dorylaimida: Qudsianematidae) associated with Picea crassifolia in China - Wu, Wen-Jia; Xu, Chun-Ling; Wang, Dong-Wei; Xie, Hui (Zootaxa, 2018)
A new species, Eudorylaimus piceae n. sp., extracted from rhizosphere soil of Picea crassifolia from Inner Mongolia, China was identified. The new species is characterized by these combined characters: body length of 1.03–1.27 mm; lip region distinctly offset; odontostyle 20–22 μm and 1.1–1.4 times the lip region diameter in length; odontophore 1.1–1.2 times the odontostyle length; basal expansion of pharynx occupying 42%–50.5% of the total neck length; genital system didelphic-amphidelphic; vulva transverse; vagina extending inwards 32%–43%; V value averaging more than 60; pars refringens vaginae with two trapezoidal sclerotizations and pars distalis vaginae weakly sclerotized; prerectum 72–107 μm long, 2.3–3.3 times the anal body diameter, and rectum 1–1.6 times the anal body diameter in length; tail conoid and bent ventrally, c’ value 1.5–1.8 and males unknown. Phylogenetic analyses based on sequences of 18S small subunit rDNA and the D2-D3 expansion region of 28S rDNA are presented.